Armazenabilidade de sementes crioulas de feijão-fava em diferentes embalagens - Wagner Fabian Gonçalves Santos (2020)
Storability of creole fava bean seeds in different packages ABSTRACT Fava beans, Phaseolus lunatus L., cultivated mainly by family farming, are of great importance in human and animal nutrition as they provide proteins and amino acids, increase income and guarantee food sovereignty for families. In the context of climate changes that have occurred, fava beans are highly rustic and adaptable to the semi-arid climate. Preserving seeds under ideal conditions, adequate humidity and temperature ensures reduced metabolic activities and seed storability. Proper seed storage and packaging contribute both to maintaining germination and seed vigor. This study aimed to evaluate through physical and physiological tests the quality of the seeds of a creole variety of fava beans in different packages and storage periods so as to guarantee the conservation of their quality in households and seed banks. The experimental design was completely randomized. The analyses were carried out at the Seed Testing Laboratory of the Federal University of Minas Gerais. In order to evaluate the quality of fava bean seeds, physical (purity, weight of 1000 seeds, degree of humidity, seed biometry, length, width, thickness, size, shape, color and retention on sieves) and physiological (germination and vigor - first count, germination speed index, fresh mass of aerial part and seedling roots, and seedling dry matter) attributes were used. The methodology was the one recommended by the Seed Analysis Rules (RAS - Brazil, 2009) and by minimum descriptors for Phaseolus lunatus L. Four repetitions of 25 seeds were used for each package. The data were submitted to analysis of variance by the F test at the 5% level in order to verify the presence of significant interaction and the simple effects of each treatment. Multiple comparison tests for the means were performed by using the Tukey tests at the level of 5% of significance between common treatments. In order to compare the control means with the common treatments, Dunnett's test was used at a 5% significance level. Regression analysis was performed so as to evaluate the effect of storage on the variables assessed. All statistical analyses were performed by using R Statistical Software. Based on the results, it can be concluded that the storage of fava bean seeds is viable in small rural properties by using impermeable packaging of aluminized polyethylene bag. The germination and vigor of the seeds decreased throughout the storage period regardless of the type of packaging. However, seeds stored in impermeable packaging or in aluminized polyethylene bags showed better results. It is not recommended to store fava bean seeds in permeable paper packaging because they had the lowest quality indexes (germination and vigor) at the end of the storage period when compared to the control and to semipermeable and impermeable types of packaging. Keywords: Phaseolus lunatus. Germination. Vigor. Packaging. Conservation.